Wsparcie informacyjne – oczekiwania rodziców wychowujących dziecko z niepełnosprawnością intelektualną - Krajczy, Sandra (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2013)
The issue of social support for the family seems to be very current and significant, especially nowadays, i.e. in the time of fast changes, globalization and consumerism. Parents raising children with intellectual disability experience many kinds of difficulties which are often impossible to deal with without external support. One of the most important forms of such help is information support, which can be defined as providing information on the child’s development, the methods of coping with difficulties, as well as education, treatment and therapy and the possibilities of support. The research group included 80 parents of children with moderate and severe intellectual disabilities. The mothers and fathers answered questions about people, institutions and organizations from which they expected to receive information support. They also stated their expectations about the kinds and forms of information support they needed.